2019
DOI: 10.5505/biodicon.2019.27928
|View full text |Cite
|
Sign up to set email alerts
|

Antifeedant Effects of Essential oil of Mentha longifolia subsp. longifolia L. HUDSON (Lamiaceae) on Subcoccinella vigintiquatuorpunctata L. (Coleoptera: Coccinellidae)

Abstract: Antifeedant activity of essential oils obtained from Mentha longifolia subsp. longifolia L. HUDSON (Lamiaceae) against S. vigintiquatuorpunctata (Coleoptera: Coccinellidae) adults that are collected from Ordu were tested in Turkey. In general, protection of plants against pests is performed using chemical insecticides, However the use of chemical insecticides on control of the insects creates serious risks on the ecosystem. Lately, scientists are focused on studies about using essential oils obtained from plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…There is a real variability in the chemical constitution of tested BOs collected from Egyptian plants if compared with the same species from other areas, depending on many differences including climate, geology, season, used part, vegetative cycle, geographical location, and the used method to extract the BO [29]. The main compounds obtained from an analysis of the BOs are similar to those of Salama et al [30] stated that Piperitenone, Cispipertone, and limonene were classified as the most valuable chemical [33], and Menthon and Piperiton components [34]. However, the classification of monoterpene piperitone as the principal compound in M. longifolia oil contrasts sharply with the other findings as the oil contained carvone or ciscarveol [35,36] as the main ingredient.…”
Section: Chemical Constituents Of Tested Bos Derived From Wild Plantsmentioning
confidence: 76%
“…There is a real variability in the chemical constitution of tested BOs collected from Egyptian plants if compared with the same species from other areas, depending on many differences including climate, geology, season, used part, vegetative cycle, geographical location, and the used method to extract the BO [29]. The main compounds obtained from an analysis of the BOs are similar to those of Salama et al [30] stated that Piperitenone, Cispipertone, and limonene were classified as the most valuable chemical [33], and Menthon and Piperiton components [34]. However, the classification of monoterpene piperitone as the principal compound in M. longifolia oil contrasts sharply with the other findings as the oil contained carvone or ciscarveol [35,36] as the main ingredient.…”
Section: Chemical Constituents Of Tested Bos Derived From Wild Plantsmentioning
confidence: 76%
“…Components of the essential oil in M. longifolia were reported 34 components by Yıldırım et al (2019) , 38 components by Akkuş et al (2021) , 39 components by Bai et al (2020) , 26 components by Kaya (2014) , and 40 components by Okut et al (2017) . In the studies, the main components of M. longifolia were identified as piperitone oxide ( Golparvar et al, 2013 ; Kakhky et al, 2009 ; Yıldırım et al, 2019 ), piperitenone oxide ( Abedi et al, 2015 ; Golparvar et al, 2013 ; Kakhky et al, 2009 ; Mkaddem et al, 2009 ; Saeidi et al, 2012 ; Yıldırım et al, 2019 ), pulegone ( Abdel-Gwad et al, 2022 ; Abedi et al, 2015 ; Akkuş et al, 2021 ; Golparvar et al, 2013 ; Kakhky et al, 2009 ; Mahmoudi, 2014 ; Mkaddem et al, 2009 ; Okut et al, 2017 ; Saeidi et al, 2012 ), menthone ( Abdel-Gwad et al, 2022 ; Akkuş et al, 2021 ; Kakhky et al, 2009 ; Kaya, 2014 ; Okut et al, 2017 ; Saeidi et al, 2012 ; Yıldırım et al, 2019 ) and 1,8-cineole ( Abdel-Gwad et al, 2022 ; Abedi et al, 2015 ; Golparvar et al, 2013 ; Kakhky et al, 2009 ; Kaya, 2014 ; Mahmoudi, 2014 ; Mkaddem et al, 2009 ; Okut et al, 2017 ). In this study, piperitone oxide, piperitenone oxide, pulegone, and 1,8-cineole were similar to the main components.…”
Section: Resultsmentioning
confidence: 99%
“…The antifungal effect of essential oils has been connected with several compounds ( Kahramanoğlu et al, 2022 ; Nazzaro et al, 2017 ). Mentha, Achillea , and Artemisia are three important genus and it has been reported that these plants contain abundant antifungal compound content ( Bai et al, 2020 ; Barış et al, 2006 ; Okut et al, 2017 ; Sharopov et al, 2012 ; Vieira et al, 2017 ; Yıldırım et al, 2019 ). Components and amounts of essential oils are known to create remarkable variations depending on part of the plant, manufacturing process, climate, geographical region, and different locations ( Bailen et al, 2013 ; Kakhky et al, 2009 ; Özgüven and Kırıcı, 1999 ).…”
mentioning
confidence: 99%
“…The plants, mainly used as a source of food and medicine in the past, have been used as tea and spice in the present day [3]. The studies on this topic have revealed that the healing properties of plants stem from various components such as essential oils [36], phenolic substances and various antioxidants [1; 16]. It is known that these components are important in the regulation of cellular ROS, antimicrobial protection and in the fight against several diseases such as cancer [20].…”
Section: Introductionmentioning
confidence: 99%